An Unexpected Role of Hyaluronic Acid in Trafficking siRNA Across the Cellular Barrier: The First Biomimetic, Anionic, Non‐Viral Transfection Method. Issue 9 (31st January 2019) - Paidikondala, Maruthibabu; Rangasami, Vignesh Kumar; Nawale, Ganesh N.; Casalini, Tommaso; Perale, Giuseppe; Kadekar, Sandeep; Mohanty, Gaurav; Salminen, Turkka; Oommen, Oommen P.; Varghese, Oommen P.
Abstract: Circulating nucleic acids, such as short interfering RNA (siRNA), regulate many biological processes; however, the mechanism by which these molecules enter the cell is poorly understood. The role of extracellular‐matrix‐derived polymers in binding siRNAs and trafficking them across the plasma membrane is reported. Thermal melting, dynamic light scattering, scanning electron microscopy, and computational analysis indicate that hyaluronic acid can stabilize siRNA via hydrogen bonding and Van der Waals interactions. This stabilization facilitated HA size‐ and concentration‐dependent gene silencing in a CD44‐positive human osteosarcoma cell line (MG‐63) and in human mesenchymal stromal cells (hMSCs). This native HA‐based siRNA transfection represents the first report on an anionic, non‐viral delivery method that resulted in approximately 60 % gene knockdown in both cell types tested, which correlated with a reduction in translation levels. Abstract : Hitchin' a ride : Hyaluronic‐acid‐induced stabilization of siRNAs via hydrogen bonding and van der Waals interactions plays a role in siRNA uptake. Mimicking this cellular trafficking mechanism enabled the delivery of RNAi molecules into two different cell lines, resulting in approximately 60 % gene knockdown. This is the first report on an anionic, non‐viral siRNA delivery method.